ANALYSIS OF STUDENTS’ M I S C O N C E P T I O N O N T H E TOPIC OF HUMAN EXCRETORY SYSTEM IN GRADE XI SMA NEGERI DISTRICT MEDAN KOTA - Carolina Savitry Hutagaol; Tri Harsono (Jurnal Pelita Pendidikan, 2016)
The purpose of this study were to analysis the presence of misconception , concept that become misconception,percentage of concept that become misconception and the source and cause of students’ misconception on thetopic of human excretory system in grade XI SMA Negeri District Medan Kota. This research type was descriptive.The samples were 168 students from 2 SMA Negeri in District Medan Kota. Data collected by using diagnostic testfollow with open reasoning and source of learning. The result show the students have misconception with conceptfunction of lungs as excretory organ was concept that highest become misconception for students. Percentage ofconcept that become misconception was 100%. The highest source and cause of misconception in this study wasbook/literature. The author proposed the students to select the book/literature that use in study.Keywords : diagnostic test, human excretory system, misconception